1981
DOI: 10.1111/j.1469-1809.1981.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on molecular mechanisms ofMcArdle's disease (muscle glycogen phosphorylase deficiency)

Abstract: McArdle's disease is due to the lack of activity of muscle glycogen phosphorylase. We investigated the presence of an inactive protein by two techniques: (a) Bidimensional protein maps, using a modification of the original O'Farrell technique allowing location of phosphorylase. (b) Purification of enzyme from crude muscle extracts, using an immunoaffinity microchromatographic procedure. Protein maps of three patients were obtained. No protein was detected at the normal (97 K) position of phosphorylase but 70 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…4). In five patients (2,5,6,9, and 10) no specific phosphorylase mRNA could be seen, whereas aldolase A mRNA was present.…”
Section: Resultsmentioning
confidence: 99%
“…4). In five patients (2,5,6,9, and 10) no specific phosphorylase mRNA could be seen, whereas aldolase A mRNA was present.…”
Section: Resultsmentioning
confidence: 99%
“…Daegelen-Proux et al [ 1 ] described the presence of an inactive protein in muscle biopsy extracts from patients with myophosphorylase deficiency by using two-dimen sional electrophoresis and immunoaffinity microchro matography.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies of myophosphorylase deficiency revealed that in most cases the protein is absent and the mRNA is missing or greatly reduced (4)(5)(6), in some patients there is a normal amount of either full-length or shorter mRNA, and in a few patients an inactive protein of normal or reduced size can be shown by immunoreaction with anti-M-GP antiserum (5)(6)(7)(8)(9). In human tissues there are three different isoforms ofglycogen phosphorylase (GP) ( 10), which are encoded by three separate genes (1 1-13).…”
Section: Introductionmentioning
confidence: 99%